Hypoxia-Inducible Factor 2-Alpha Mediated Gene Sets Differentiate Pulmonary Arterial Hypertension - Zhu, Jinsheng; Zhao, Li; Hu, Yadan; Cui, Guoqi; Luo, Ang; Bao, Changlei; Han, Ying; Zhou, Tong; Lu, Wenju; Wang, Jian; Black, Stephen M.; Tang, Haiyang (Frontiers in Cell and Developmental Biology, 2021)
Objectives: HIF2α carrys a big weight in the regulation of endothelial dysfunction, cell proliferation, migration, and pulmonary vascular remodeling in pulmonary hypertension. Our previous studies demonstrated that conditional and inducible deletion of HIF2α in mouse lung endothelial cells, dramatically protected the mice against vascular remodeling and the development of pulmonary arterial hypertension (PAH). Here, we provide a novel transcriptome insight into the impact of HIF2α in PAH pathogenesis and the potential to use HIF2α-mediated gene set to differentiate PAH human subjects. Methods: Using transcriptome data, we first tapped the value of the difference in gene expression profile between wild type (WT) and Hif2a knockdown (KD) cell lines. We considered the deregulated genes between WT and Hif2a-KD cells as HIF2α influenced genes. By examining the lung tissue transcriptome data set with nine controls and eight PAH patients, we evaluated the HIF2α regulatory network in PAH pathogenesis to further determine the identification ability of HIF2α-mediated gene sets in human PAH subjects. On the other hand, using peripheral blood mononuclear cells (PBMCs) transcriptome data from PAH patients and healthy controls, we further validated the potential of the HIF2α-mediated PBMC gene sets as a possible diagnostic tool for PAH. To verify the ability of HIF2α-mediated gene sets for the identification of PAH, endothelial cell-specific Phd2 knock out mice with spontaneous pulmonary hypertension were used for reverse validation experiments. Results: 19 identified GO biological process terms were significantly correlated with the genes down-regulated in Hif2a-KD cells, all of which are strongly related to the PAH pathogenesis. We further assessed the discriminative power of these HIF2α-mediated gene sets in PAH human subjects. We found that the expression profile of the HIF2α-mediated gene sets in lung tissues and PBMCs were differentiated both between controls and PAH patients. Further, a significant positive correlation was observed between hypoxia and Phd2 deficiency mediated gene set expression profiles. As expected, 7 of the 19 significantly down-regulated GO terms in Hif2a-KD cells were found to overlap with the up-regulated GO gene sets in Phd2EC-/- mice compared to WT controls, suggesting opposing effects of HIF2α and PHD2 on PAH pathogenesis.